O contexto das brincadeiras das crianças ribeirinhas da Ilha do Combu - TEIXEIRA, Sônia Regina dos Santos (2016)
This study describes the context of plays among preschoolers on Combu Island, near Belém, PA, focusing on aspects of physical and social environment as well as the main activities of adults and the peculiarities of the make-believe play. Thirteen children (11 boys and 2 girls,) aged between four and five years old participated in the research. The children and their relatives were interviewed, and the group was observed while playing at their homes. The play was analyzed with reference to the themes, their peer group, the location, the objects involved, and the implicit meaning in each activity. Although the children were in close contact with an urban setting, they showed a strong affinity with their riverine environment.